Matrix attachment regions as a tool to influence plant transgene expression - Dolgova, Anna Sergeevna (3 Biotech, 2019)
The inclusion of special regulatory sequences known as matrix attachment regions (MARs) in transgene constructs has been suggested as a possible approach to stabilise the expression of foreign heterological genes. The present review provides a brief summary regarding the MARs that have been used in investigations studying their influence on plant transgene expression in different plants with different promoters and reporter genes, and the comparison of these investigations.